Wage Equality in the Perspective of Justice for Women Workers - Lusiana Adela Nugraheni; Nur Sabela Rahmawati (Fakultas Hukum Universitas Widya Mataram, 2023)
Labor problems in the world are not limited to problems between workers or workers and companies. Another issue that requires special attention is wages. The problem of wages is often the main discourse on the equality of wages for male and female workers. The type of research used in compiling this paper is juridical-normative. The normative juridical research method is a library law research conducted by examining secondary data including primary legal materials and secondary legal materials Labor law has not yet accommodated equal wages. The equality defined in this law is limited to work placements. Even though in Government Regulation Number 36 of 2021 equality of wages has been guaranteed, However, with no legal basis above it, this PP does not have a strong legal basis. Thus, it can be judged that the Manpower Law is actually not aligned with international legal instruments and the spirit of a decent living in the 1945 Constitution. In terms of the policy aspects carried out by the Ministry of Manpower in the national strategy, it is not yet aligned with the final objectives achieved and requires optimization in the future. Labor regulations in Indonesia have not accommodated equal pay. Equality that is accommodated is only equal in terms of opportunity and access to employment. policy, the Ministry of Manpower has not yet accommodated equal wages as a goal in the global instrument. This condition is possible because national legal instruments have not regulated gender equality. Keywords: Wages Equality, Employment, Women Workers